São Vicente (RN) nos primeiros anos da TV: Memória, sociabilidade e cotidiano - Ribeiro, Ana Paula de Araujo (2012)
The present work aims to reflect on the everyday and its Vincentian practices of sociability in the early years of the presence of television in the city of São Vicente (RN), from the memories of the protagonists who witnessed the first insertion of TV set sin the beginning sof 1970s.Thus, the research was guided by some questions deemed relevant to the study in order to understand the most significant changes in the daily Vincentian boosted by the arrival of television in some private houses, which soon became a meeting place, recreation and sociability. At that time, filled the role of TV unites and brings people together. These houses, reinvented in spaces of sociability, were sanctioned by the various actors who gathered daily to include television programming. This popularity of television was measured by the joint efforts of people who moved their homes to homes that had this technical device. Each home with their uniqueness sand peculiarity, which attracted the population frequency f these spaces were frequent. Of course people still sit on the sidewalks, to be held the night rides in the streets and square, but soon came to the program schedule Preferred came into leaving their homes or to homes that had TV, watch them in the design of audiovisual programs. We use the oral memory as the principal methodology in order to interpret the memories recounted by people who lived in that time period studied. For this purpose we constructed a narrative that highlights the categories memory, media, social practices, everyday life and thus has the theoretical and methodological contributions of authors of humanities and social sciences its main foundation. In field research in the use of in-depth interviews, since the narratives of our research is interviewed. The importance of a study of such order, is not only in understanding the TV as an essential mediator for the interaction of individuals in society, from 1970 in São Vicente (RN), but also for the unveiling of his relationship with the daily routines of the Vincentians, founded in environments and symbols that regulated the conduct and reordered the social practices and sociability of these subjects. In this sense, the making of a work on the presence of TV in the city of São Vicente (RN) is also of paramount importance for the history of this media at the national level, since this is nothing more than a set of multiple stories